Coupling of nitrogen-vacancy centers to photonic crystal cavities in monocrystalline diamond - Faraon, Andrei; Santori, Charles; Huang, Zhihong; Acosta, Victor M; Beausoleil, Raymond G (Physical review letters, 2012)
The zero-phonon transition rate of a nitrogen-vacancy center is enhanced by a factor of ∼70 by coupling to a photonic crystal resonator fabricated in monocrystalline diamond using standard semiconductor fabrication techniques. Photon correlation measurements on the spectrally filtered zero-phonon line show antibunching, a signature that the collected photoluminescence is emitted primarily by a single nitrogen-vacancy center. The linewidth of the coupled nitrogen-vacancy center and the spectral diffusion are characterized using high-resolution photoluminescence and photoluminescence excitation spectroscopy.